2006
DOI: 10.1093/toxsci/kfl169
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Antioxidant Defenses may Contribute to Ochratoxin A Toxicity and Carcinogenicity

Abstract: Ochratoxin A (OTA) is a renal carcinogen in rodents. Its human health significance is unclear. It likely depends upon the mechanism of carcinogenesis. In a previous microarray study a reduction in nuclear factor-erythroid 2 p45-related factor 2 (Nrf2)-dependent gene expression was observed in the kidney but not in the liver of rats fed OTA up to 12 months. Nrf2 regulates detoxification and antioxidant gene expression. The present report shows that OTA decreased the protein expression of several markers of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
89
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(104 citation statements)
references
References 45 publications
12
89
2
1
Order By: Relevance
“…OTA-induced oxidative stress and ensuing DNA damage in combination with enhanced cell proliferation could increase the likelihood of neoplastic transformation (29). The presence of oxidative DNA damage, as also suggested by earlier findings (30)(31)(32), is supported by the up-regulation of the p53 pathway genes SUPT16H in both strains, MDM2 and CHEK2 in Eker rats, and RBBP6 in wild-type rats as well as by the time-dependent down-regulation of HSP 40-3, CN1, MSRA, and MGST1, responsible for the protection of cells against oxidative stress. Indeed, recent findings showed that overexpression of glia maturation growth factor h (GMFB) resulted in reduced antioxidant enzyme activities, subsequent accumulation of H 2 O 2 , and finally enhanced oxidative injury of renal proximal tubular cells (33).…”
Section: Discussionsupporting
confidence: 52%
“…OTA-induced oxidative stress and ensuing DNA damage in combination with enhanced cell proliferation could increase the likelihood of neoplastic transformation (29). The presence of oxidative DNA damage, as also suggested by earlier findings (30)(31)(32), is supported by the up-regulation of the p53 pathway genes SUPT16H in both strains, MDM2 and CHEK2 in Eker rats, and RBBP6 in wild-type rats as well as by the time-dependent down-regulation of HSP 40-3, CN1, MSRA, and MGST1, responsible for the protection of cells against oxidative stress. Indeed, recent findings showed that overexpression of glia maturation growth factor h (GMFB) resulted in reduced antioxidant enzyme activities, subsequent accumulation of H 2 O 2 , and finally enhanced oxidative injury of renal proximal tubular cells (33).…”
Section: Discussionsupporting
confidence: 52%
“…Besides, in some studies, an inhibition of the pathways regulated by Nrf2 have been described in kidney but not in liver (Marin-Kuan et al, 2006;Cavin et al, 2007). Thus, the protection of OTA against AFB1 genotoxicity would not be explained through this mechanism.…”
Section: Discussionmentioning
confidence: 97%
“…The Ochratoxins are mycotoxins produced by some Aspergillus species such as A. Ochraceus and A. Niger, whereas some Penicillium species such as P. Verrucosum and P. Carbonarius are also found to produce Ochratoxins (32). Among all the types mentioned, Ochratoxin A is the most common and it has the highest degree of toxicity (33)(34)(35). The Ochratoxins can be found in cereals, coffee, dried fruit, and red wine.…”
Section: Types Of Mycotoxins and Their Natural Commoditiesmentioning
confidence: 99%